The Cost of Depression-Related Presenteeism in Resident Physicians - Rosen, Tracey (Acad Psychiatry, 2017)
OBJECTIVE: The authors aimed to assess the level of presenteeism, defined as a worker being present but not functioning at full capacity, related to depression among interns and determine the associated economic cost. METHODS: Interns from 55 universities nationwide received an invitation to participate in a prospective longitudinal study. The authors assessed participants’ depressive symptoms before residency and at 12 months using the nine-item Patient Health Questionnaire (PHQ-9). They assessed performance associated with presenteeism at 12 months of residency using the Health and Work Performance Questionnaire. RESULTS: The study enrolled 3127 interns. Mean PHQ score increased significantly from 2.74 before residency to 5.33 at 12 months of residency (p=0.26, p<0.001). A PHQ score of 10 or above correlated significantly with presenteeism during residency (p=-1.00, p<0.0001). Mean performance levels decreased (i.e., presenteeism increased) as depression severity levels increased from minimal depression (74.8%) to mild (68.9%), moderate (64.8%), moderately severe (59.8%) and severe depression (56.3%). If depression severity levels were unchanged from baseline, the mean presenteeism would have been 3.5% lower during residency. With the annual productivity of residents estimated to have a value of $296,000, a 3.5% increase in productivity value would result in a $1.2 billion gain across all resident physicians practicing each year. CONCLUSIONS: The economic cost of presenteeism associated with depression caused by residency is substantial. As residency programs, institutions, and accrediting agencies weigh the costs and benefits of interventions and system changes to reduce depression in residency, they should consider the hidden productivity cost of depression.